2018
DOI: 10.1042/cs20180563
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of autophagy by 3-MA attenuates hyperuricemic nephropathy

Abstract: Autophagy has been identified as a cellular process of bulk degradation of cytoplasmic components and its persistent activation is critically involved in the renal damage induced by ureteral obstruction. However, the role and underlying mechanisms of autophagy in hyperuricemic nephropathy (HN) remain unknown. In the present study, we observed that inhibition of autophagy by 3-methyladenine (3-MA) abolished uric acid-induced differentiation of renal fibroblasts to myofibroblasts and activation of transforming g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 75 publications
2
69
0
Order By: Relevance
“…It was demonstrated that 70% of urate eliminated occurs in the kidneys, and decreased eGFR would result in elevated levels of SUA 48. However, UA could induce oxidative stress, trigger activation of RAAS and inflammation, cause endothelial dysfunction, and thus subsequently lead to the decline in eGFR 35 49 50. The persistently high level of SUA predicts the high risk of developing CKD 51.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that 70% of urate eliminated occurs in the kidneys, and decreased eGFR would result in elevated levels of SUA 48. However, UA could induce oxidative stress, trigger activation of RAAS and inflammation, cause endothelial dysfunction, and thus subsequently lead to the decline in eGFR 35 49 50. The persistently high level of SUA predicts the high risk of developing CKD 51.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show that increased serum uric acid often precedes the deterioration of chronic kidney disease (CKD) 3 . Moreover, basic studies demonstrate that chronic uric acid injury to the kidney is sufficient to trigger renal tubular damage, interstitial fibrosis, glomerulosclerosis and urate crystal deposition, leading to hyperuricemic nephrology (HN) 1,4,5 . Therefore, further exploration of the mechanism leading to hyperuricemic nephrology will aid in the development of new strategy for treatment of HN.…”
Section: Introductionmentioning
confidence: 99%
“…Tubulointerstitial fibrosis is thought to be the primary pathogenesis for progressive HN [4][5][6] . Diseased proximal tubules act as a driving force for interstitial fibrosis through activation of autocrine and paracrine signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common autophagy-inhibiting molecules could be categorized into four groups according to their mode of action: (1) Repressors of autophagosome formation, class III PI3K inhibitors, e.g., 3-methyladenine (3-MA), Wortmannin, LY294002, SAR405 and Viridiol that block the formation of autophagosome. (2) Repressors of lysosomal acidification: Lysosomotropic agents, such as Cloroquine (CQ), Hydroxychloroquine (HCQ), Lys0569, and Monensin prevent acidification of lysosomes and thus inhibit degradation of the cargo in the autophagosomes; (3) Inhibitors of autophagosome-lysosome fusion: Vacuolar-ATPase inhibitors, Bafilomycin and Concanamycin variants that interfere with the fusion of autophagosomes with lysosomes; (4) Silencers of transcription of autophagy-related genes: it has been demonstrated, indeed, that by means of siRNA-or miRNA-mediated silencing strategies, knockdown of autophagy-related genes can be achieved with subsequent inhibition of autophagic activity [74][75][76][77][78][79].…”
Section: Targeting Autophagy As a Cancer Treatmentmentioning
confidence: 99%